2014
DOI: 10.3382/ps.2014-04291
|View full text |Cite
|
Sign up to set email alerts
|

Growth, efficiency, and yield of commercial broilers from 1957, 1978, and 2005

Abstract: The effect of commercial selection on the growth, efficiency, and yield of broilers was studied using 2 University of Alberta Meat Control strains unselected since 1957 and 1978, and a commercial Ross 308 strain (2005). Mixed-sex chicks (n = 180 per strain) were placed into 4 replicate pens per strain, and grown on a current nutritional program to 56 d of age. Weekly front and side profile photographs of 8 birds per strain were collected. Growth rate, feed intake, and measures of feed efficiency including feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
426
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 608 publications
(456 citation statements)
references
References 34 publications
12
426
0
18
Order By: Relevance
“…Nevertheless, there is anecdotal evidence also to show the involvement of genetics in decreasing feed spillage. For instance, although it was not the aim of the experiment to examine differences in feed spillage between breeds, relatively high feed wastage was observed by Zuidhof et al (2014) in less selected broiler breeds compared to modern breeds (i.e. birds which have a genotype similar to what could be expected to be grown commercially nowadays).…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, there is anecdotal evidence also to show the involvement of genetics in decreasing feed spillage. For instance, although it was not the aim of the experiment to examine differences in feed spillage between breeds, relatively high feed wastage was observed by Zuidhof et al (2014) in less selected broiler breeds compared to modern breeds (i.e. birds which have a genotype similar to what could be expected to be grown commercially nowadays).…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
“…Much progress has been made in artificial selection technologies over the last century: from mass selection to the use of pedigree charts and hybridisation, to the introduction of selection indices and artificial insemination, to the development of modern breeding value estimation techniques (Rishell 1997;Muir and Aggrey 2003). Consequently, Zuidhof et al (2014) showed chicken broiler growth rate to have increased by over 400 % between the years of 1950 and 2005 ( Fig. 1), when genetically representative birds of those years were grown in identical environments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited in vivo research has shown that increased IP can lead to increased bacterial translocation , coccidiosis (Chapman, 2014) and lameness (Wideman et al, 2012) in chickens. These diseases can impact health and welfare leading to reduced efficiency and economic loss (Zuidhof et al, 2014).…”
Section: Introductionmentioning
confidence: 99%